We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**+1 **

The solution to this is quite involved:

Solve for x:

-9 sqrt(x) - 5 x + x^(3/2) = 35

Subtract 35 from both sides:

-35 - 9 sqrt(x) - 5 x + x^(3/2) = 0

Simplify and substitute y = sqrt(x).

-35 - 9 sqrt(x) - 5 x + x^(3/2) = -35 - 9 sqrt(x) - 5 (sqrt(x))^2 + (sqrt(x))^3

= y^3 - 5 y^2 - 9 y - 35:

y^3 - 5 y^2 - 9 y - 35 = 0

The left hand side factors into a product with two terms:

(y - 7) (y^2 + 2 y + 5) = 0

Split into two equations:

y - 7 = 0 or y^2 + 2 y + 5 = 0

Add 7 to both sides:

y = 7 or y^2 + 2 y + 5 = 0

Substitute back for y = sqrt(x):

sqrt(x) = 7 or y^2 + 2 y + 5 = 0

Raise both sides to the power of two:

x = 49 or y^2 + 2 y + 5 = 0

Subtract 5 from both sides:

x = 49 or y^2 + 2 y = -5

Add 1 to both sides:

x = 49 or y^2 + 2 y + 1 = -4

Write the left hand side as a square:

x = 49 or (y + 1)^2 = -4

Take the square root of both sides:

x = 49 or y + 1 = 2 i or y + 1 = -2 i

Subtract 1 from both sides:

x = 49 or y = -1 + 2 i or y + 1 = -2 i

Substitute back for y = sqrt(x):

x = 49 or sqrt(x) = -1 + 2 i or y + 1 = -2 i

Raise both sides to the power of two:

x = 49 or x = -3 - 4 i or y + 1 = -2 i

Subtract 1 from both sides:

x = 49 or x = -3 - 4 i or y = -1 - 2 i

Substitute back for y = sqrt(x):

x = 49 or x = -3 - 4 i or sqrt(x) = -1 - 2 i

Raise both sides to the power of two:

x = 49 or x = -3 - 4 i or x = -3 + 4 i

-9 sqrt(x) - 5 x + x^(3/2) ⇒ -9 sqrt(-4 i - 3) - 5 (-3 - 4 i) + (-3 - 4 i)^(3/2) = -5 + 40 i:

So this solution is incorrect

-9 sqrt(x) - 5 x + x^(3/2) ⇒ -9 sqrt(4 i - 3) - 5 (-3 + 4 i) + (-3 + 4 i)^(3/2) = -5 - 40 i:

So this solution is incorrect

-9 sqrt(x) - 5 x + x^(3/2) ⇒ -9 sqrt(49) - 5 49 + 49^(3/2) = 35:

So this solution is correct

The solution is:

**x = 49**

Guest Jul 2, 2018

#2**+1 **

Given that x is an integer such thatx * √x - 5x - 9 * √x = 35 , find x.

\(x\sqrt x - 5x - 9\sqrt x = 35\qquad x\ge 0\\ let\;\;y=\sqrt x\qquad \qquad \qquad y\ge 0\\ y^2*y-5y^2-9y=35 \\ y^3-5y^2-9y=35 \\ y^3-5y^2-9y-35 =0\\ \)

I am told that there is an integer solution to this so how do I find it ?

Well I know y must be positive, that makes it easier.

The solution must be a factor of 35.

So it has to be 1 or 5 or 7 or 35.

1-5-9-35 = -48 so 1 is not right

5^3-5*5^2-9*5-35 = -80 so 5 is not correct

7^3-5*7^2-9*7-35 = 0 so 7 is a root

35^3-5*35^2-9*35-35 = 36400 so 35 is not a root.

So the only poisitive integer solution is y=7

so

\( x=y^2 \\x= 49\)

-------------

Graphical check :

When I graphed \(y^3-5y^2-9y-35=0\)

this is the the result ... just remember that the axis have been reversed.

I know this is a cubic so the cruve cannot turn around again so the only answer is y=7

Which means that x=49.

Melody Jul 2, 2018